Estudiar historia desde la literatura : la invasión de Francia - Rodriguez Garrido, Juan Esteban (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
The invasion of France is one of the most relevant events in World War II as it represents, possibly, Hitler´s biggest international achievement and the zenit of is power in Europe. It has been, for that same reason, a matter that has found an important echo in Literature. In that sense, the cooperation between Literature and History, for a better understanding of the latter, reveals itself as a relevant teaching possibility. That is what this article proposes, a reflexion about the connection between History and Literature, and an explanation on the german invasion of France illustrated with literary texts that help to understand those historical events here analized.